The Hype Handbook - Schein, Michael (McGraw Hill-Ascent Audio, 2021)
Influencers have always deployed the power of hype to get what they want. But never in history have people been so susceptible to propaganda and persuasion as they are now. Hype truly runs our world. Imagine if you could generate and leverage hype for positive purposes-like legitimate business success, helping people, or effecting positive change in your community. Michael F. Schein teaches you how. In The Hype Handbook, the notorious marketing guru provides twelve fundamental strategies for creating and leveraging hype for good, including ways to: attract attention from people that matter; create a community of acolytes to further your cause; create an atmosphere of curiosity and intrigue; sell your message with the skill of a master; and create a step-by-step "manifesto." Citing the latest research in psychology, sociology and neuroscience, Schein breaks the concept of hype down into a simple set of strategies, skills, and techniques-and illustrates his methods through stories of the world's most effective hype artists, including American propagandist Edward Bernays, Alice Cooper manager Shep Gordon, celebrity preacher Aimee Semple McPherson, Spartan Race founder Joe De Sena, and digital guru Gary Vaynerchuk